Research progress of biomarkers in evaluating the severity and prognostic value of severe pneumonia in children - Gong, Weihua; Gao, Kaijie; Shan, Zhiming; Yang, Liu; Fang, Panpan; Li, Ci; Yang, Junmei; Ni, Jiajia (Frontiers in Pediatrics, 2024)
Pneumonia is a serious and common infectious disease in children. If not treated in time, it may develop into severe pneumonia. Severe pneumonia in children is mainly characterized by hypoxia and acidosis, often accompanied by various complications such as sepsis and multiple organ dysfunction. Severe pneumonia has a rapid onset and progression, and a high mortality rate. Biomarkers assist clinicians in the early diagnosis and treatment of patients by quickly and accurately identifying their conditions and prognostic risks. In this study, common clinical and novel biomarkers of severe pneumonia in children were reviewed, and the application value of biomarkers related to the severity and prognosis of severe pneumonia in children was evaluated to provide help for early identification and precise intervention by clinicians.